Anthropomorphism and the Construction of Identity in Beast-themed Folk Tales: A Study of Lutung Kasarung, Beauty and the Beast, and The Frog Princess - Sekar Ayuning Prawesti; Hana Farida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study discusses how anthropomorphism is used in constructing themes of identity, disguise, and transformation through three folk tales: Lutung Kasarung (Indonesia), Beauty and the Beast (France), and The Frog Princess (Russia). All three feature beasts or non-human characters who have human-like traits, behaviours, and the ability to think and speak. Through a qualitative approach with narrative analysis and Stewart Guthrie's (1993) theory of anthropomorphism, this article shows that non-human forms are used as a form of disguise for true identity, as well as a means of conveying inner conflict and moral values. The findings show that the three folk tales analysed in this study have narrative patterns similar to cross-cultural patterns. This pattern consists of a curse, which is the cause of identity change; disguise, which is the process of identity change; and transformation, which is the end of the story and the resolution of the problem.